A case of renal hypouricemia due to T217M mutation in SLC22A12 incidentally associated with IgA nephropathy - Yoshimasa Sakurabu; Haruhito A. Uchida; Toshihisa Tahara; Tomohiko Asakawa; Haruka Yamasaki; Katsuyoshi Katayama; Shugo Okamoto; Yasuhiro Onishi; Natsumi Matsuoka‐Uchiyama; Keiko Tanaka; Hidemi Takeuchi; Kenji Tsuji; et al. (Clinical Case Reports, 2024)
Key Clinical Message A T217M heterozygous mutation in the SLC22A12 gene caused renal hypouricemia; this patient with IgA nephropathy had no findings other than IgA nephropathy on renal biopsy. Hypouricemia was susceptible to oxidative stress, but IgA nephropathy in the patient with hypouricemia could be treated with steroid pulse therapy without adverse events.